Measurement of the burdens of neonatal disorders in 204 countries, 1990–2019: a global burden of disease-based study - Xin, Juan; Luo, Yiwen; Xiang, Wanwan; Zhu, Sijing; Niu, Hui; Feng, Jiayuan; Sun, Landi; Zhang, Boxing; Zhou, Xihui; Yang, Wenfang (Frontiers in Public Health, 2024)
Background Neonatal disorders are facing serious public health challenges. Previous studies were based on limited data sources and had a narrow geographical scope. We aim to understand the trends of alteration in burden of neonatal disorders over a period of 1990 to 2019 in 204 countries and territories. Methods Data was investigated from the Global Burden of Disease Study 2019. Firstly, we visualized the burden of neonatal disorders using the number of cases and the age-standardized incidence rate (ASIR), death rate (ASDR) and disability-adjusted life years (ASR-DALYs) from 1990 to 2019. Secondly, estimated annual percentage changes (EAPCs) were used to evaluate temporal trends of disease burden during different periods. Finally, the sociodemographic index (SDI) and human development index (HDI) were used to determine whether there exists a correlation between socioeconomic development level, human development level and potential burden consequences. Results Overall, in the past 30 years, the ASIR trends remained relatively steady, while the ASDR and ASR-DALYs had declined. However, the burden of neonatal disorders varied greatly in various regions and countries. Among 21 regions, the ASIR trend had the largest increase in Central Latin America (EAPC=0.42, 95%CI=0.33-0.50). Conversely, the ASDR and ASR-DALYs experienced the largest decrease in Central Europe (EAPC=-5.10, 95%CI=-5.28-4.93) and East Asia (EAPC=-4.07, 95%CI=-4.41-3.73), respectively. Among 204 countries, the ASIR (EAPC=3.35, 95%CI=3.13-3.56) trend in Greece displayed the most significant increase, while the ASDR (EAPC=1.26, 95%CI=1.01-1.50) and ASR-DALYs (EAPC=1.26, 95%CI=1.03-1.49) trend in Dominica experienced the most substantial rise. Besides, there was a strong correlation between the EAPC in ASIR, ASDR as well as ASR-DALYs and SDI or HDI in 2019, with some exceptions. And countries with elevated levels of HDI underwent a faster rise in ASDR and ASR-DALYs for neonatal disorders. Conclusions Although the burdens of neonatal disorders show a downward trend from 1990 to 2019, it was still not optimistic. It is necessary to implement a multi-pronged approach to reduce the increasing burden of neonatal disorders.